KEDAWUNG (Parkia timoriana) DAN KERABATNYA DI JAWA; PETIR (P. intermedia) DAN PETAI (P. speciosa) - Rugayah Rugayah; Arief Hidayat; Udjang Hafid (BERITA BIOLOGI, 2014)
Kedawung is a member of the plant genus of Parkia (Mimosaceae). It has important value as traditional medicine and currently has been included in the Indonesian list of endangered medicinal plant species. There are two closely related species to Kedawung in Java: P. intermedia and P. speciosa. Parkia intermedia has long been assumed to be a hybrid between P. speciosa and P. timoriana. The species has leaflets linear-oblong and obtuse apex in mature foliage resemble P. speciosa, but has more numerous leaflets, linear-falcate, and acute apex in its juvenile leaflets similar to P. timoriana. Thus Hopkins (1992) included Petir as uncertain species. The aim of this study was to assess its current existing populations, to clarify the taxonomic status and to evaluate the similarity between kedawung and its related species. Exploration, morphology and leaf anatomical studies, as well as phenetic analysis have been conducted. The results indicated that morphology and leaf anatomical characters can be used to distinguish P. timoriana, P. intermedia and P. speciosa as different species, and P. intermedia was more closely related to P. speciosa than to P. timoriana.